Self Assesment Gizi Pada Ibu Hamil Trimester III Di Puskesmas Mangasa Kota Makassar - Subriah, Subriah; Hidayati, Hidayati; Ningsi, Agustina; Sonda, Maria (Media Implementasi Riset Kesehatan, 2024)
ABSTRACT The nutritional status of pregnant women greatly affects the growth of the fetus in the womb. If the nutritional status of the mother is poor, both before pregnancy and during pregnancy, it will cause low birth weight (LBW). Besides, it will result in inhibition of fetal brain growth, anemia in newborns, newborns easily infected, abortion and so on.The results of research conducted by Subriah, et al, 2018 with the title Relationship of Knowledge and Nutritional Status of Third Trimester Pregnant Women at the Mangasa Health Center Makassar City Show that Ha is accepted where the p-value (0.00) <α-value (0.05) with a value of phi (µ) = 0.658 (66%) so it can be assumed that there is a relationship between knowledge and the nutritional status of third trimester pregnant women at the Mangasa Health Center Makassar City. The purpose of the service is to increase the knowledge of pregnant women in the third trimester about nutrition in pregnant women, to increase the motivation of pregnant women for regular antenatal care checks so that if there is a problem with the nutrition of pregnant women, they can be handled immediately and pregnant women can conduct a nutritional self-assessment in their pregnancy. The service method is carried out in the form of education and role play, conducting pretest and posttest. This activity lasts for 8 months starting from the preparation stage to evaluation and publication. The Community Service Team together with students and resource persons provided material through leaflets, food cards to 45 third trimester pregnant women. The outputs of this activity were leaflets, articles. The results of activities for 45 pregnant women in the third trimester After pre and post implementation of nutritional knowledge for pregnant women There were 38 (84.5%) mothers who had high scores, 6 had moderate scores (13.3%) and there was still 1 pregnant woman. (2.2%) regarding nutrition of pregnant women in the third trimester at the Mangasa Public Health Center Makassar. Keywords: Third trimester of pregnancy, self assessment, nutritional status   ABSTRAK Status gizi ibu hamil sangat mempengaruhi pertumbuhan janin dalam kandungan. Apabila status gizi ibu buruk, baik sebelum kehamilan dan selama kehamilan akan memyebabkan berat badan lahir rendah (BBLR). Disamping itu akan mengakibatkan terhambatnya pertumbuhan otak janin, anemia pada bayi baru lahir , bayi baru lahir mudah terinfeksi, abortus dan sebagainya. Hasil penelitian yang dilakukan oleh Subriah, dkk, 2018 dengan Judul Hubungan Pengetahuan Dengan Status Gizi Ibu Hamil Trimester III Di Puskesmas Mangasa Kota Makassar Menunjukkan Ha diterima dimana nilai p-value (0,00)<α-value (0,05) dengan nilai phi (µ) =0,658 (66%) sehingga dapat diasumsikan bahwa terdapat hubungan pengetahuan dengan status gizi ibu hamil trimester III di Puskesmas Mangasa Kota Makassar. Tujuan pengabdian adalah Meningkatkan pengetahuan ibu hamil trimester III tentang gizi pada ibu hamil, meningkatkan motivasi ibu hamil untuk pemeriksaan antenatal care teratur sehingga jika terjadi permasalahan dengan gizi ibu hamil dapat segera ditangani dan ibu hamil dapat melakukan self assessment gizi pada kehamilannya. Metode pengabdian dilaksanakan dalam bentuk edukasi dan role play, melakukan pretest dan posttest. Kegiatan ini berlangsung selama 8 bulan yang dimulai tahap persiapan sampai evaluasi dan publikasi. Tim Pengabmas bersama mahasiswa dan narasumber memberikan materi melalui leaflet, food card kepada 45 ibu hamil trimester III, Adapun luaran kegiatan ini adalah leaflet, artikel. Hasil kegiatan pada 45 ibu hamil trimester III Setelah dilaksanakan pre dan post tentang pengetahuan gizi pada ibu hamil. Tujuan dari pengabdian Masyarakat tercapai dengan tercapainya target yaitu peningkatan pengetahuan ibu hamil tentang gizi pada ibu hamil trimester 3 di Puskesmas Mangasa Kota Makassar. Kata Kunci: Kehamilan Trimester III, Self assessment, , Status gizi